PERANCANGAN DESAIN KEMASAN POTENSI WISATA KULINER DESA NAGREG KENDAN KABUPATEN BANDUNG - Nabila Azmi, Hana; Denny Nugraha, Novian; Soedewi, Sri (eProceedings of Art & Design, 2024)
Nagreg Kendan Village is a village that is currently being developed to becomea tourist destination. Besides its natural and cultural tourism potentials, Nagreg KendanVillage also has culinary tourism from several Micro, Small, and Medium Enterprises(MSME) actors that produce village flagship culinary products. However, the strategies toincrease attractiveness and selling power of the culinary tourism potentials in the villageare still minimal, so it is not widely known among the public, especially tourist. Thepackaging used mostly still uses simple packaging, does not yet display the visual identityof Nagreg Kendan Village and the characteristic of the product. The purpose of thisresearch is to create packaging design to introduce it to public, especially tourist, increaseattractiveness and selling power, as well as to become a characteristic of the culinarytourism potentials of Nagreg Kendan Village. The data collectionmethods used incompiling this final assignment report are: observation, interviews, and literature review. Keywords: Packaging design, Nagreg Kendan Village, Culinary tourism